The effect of work environment conditions on the performance of workers in Lebanese private hospitals during the Lebanese financial crisis: the case of private hospitals in North Lebanon - Fathallah, Ghassan Fawaz; Kamal-El-Din, Khaled (Journal of Economic, Administrative and Legal Sciences, 2023)
The aim of this research is to determine the effect of work environment conditions on the performance of workers in Lebanese private hospitals in North Lebanon during the Lebanese financial crisis. A sample of 95 employees of various positions in private hospitals in North Lebanon (Northern Hospital, Moawad Hospital, Our Lady Hospital, North Lebanon Hospital) was studied. The descriptive analytical approach was chosen for this research. The data was analyzed using the SPSS statistical program, and descriptive and analytical statistics were used in the analysis process. The results showed that there is a direct, statistically significant effect of the physical and behavioral conditions of the work environment on the performance of workers in private hospitals in northern Lebanon during the financial crisis in Lebanon.